The Reality of University Education in Jordan from the Viewpoint of Faculty Members - M. Tawarah, Haroon.; Mahasneh, Omar. M. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the reality of university education in Jordan from the viewpoint of faculty members and to discover whether there are differences due to the gender variable.To answer the study questions, the two researchers selected the study sample in a stratified random manner, and it consisted of (137) faculty members, from the universities of the South (Al-Hussein, Mutah, Tafila, and Al-Balqa’ colleges (Al-Shoubak, Maan, Aqaba)) for the first semester of the academic year 2019/2020. The two researchers developed a questionnaire that consisted of (44) paragraphs in its final form distributed in following the four areas: (curricula, students, faculty members, and regulations). To ensure thevalidity of the study, the two researchers presented them on a group of arbitrators, and the results of the study were as follows:Achieving university programs at the general level, for the four areas combined at a moderate level, Achieving university programs for the areas of curricula and regulations with a medium degree, and students and faculty members with a poor degree and There is no effect of gender on the level of faculty members' assessment of the questionnaire.